Engineering Ethics:Decision Making Using Fundamental Canons - Baligar, Preethi; Joshi, Gopalkrishna (Journal of Engineering Education Transformations, 2025)
An engineering professional’s work demands that the technological solutions designed to solve practical problems of society are addressing the safety, health and welfare of the public. An engineer thus works in an environment where equally competing considerations for different stakeholders need to be accounted for before providing uncompromised solutions. In such a professionally obligatory setting, ethical dilemmas come into foreplay which will decide the course of action which the problem solver will seek to take. However, the ethical problems are ill-structured and lack a set of prescriptive and enumerable solutions. Thus, the professionals need to be trained in exploring the solution space of problems related to engineering ethics during their formative four years. An aim to achieve this will require engineering educators to include of the principles of Engineering Ethics is the curriculum. The objective of this paper is to explore the existing solution space for the curriculum design, content and assessment of ethics instruction. It also presents the approach followed in designing a module on Engineering Ethics in an introductory freshman course in our university. We have designed an assessment in which the students are required to provide a resolution to the ethical dilemma by basing their decision on fundamental canons of National Society of Professional Engineers (NSPE). From the results we conclude that students are able to identify and resolve ethical dilemmas which lie in the domain of public welfare, health and safety more than the others.